Prevalence of dental caries based on gender, age, Black’s classification and its distribution on different teeth - Hong, Steven Tan Jun; Fadil, Mohammad Richata; Aripin, Dudi (Universitas Padjadjaran, 2013)
Introduction: Dental caries (tooth decay) is probably the most common chronic disease in the world. Greene Vardiman Black in the end of nineteenth century presented G. V. Black’s classification. The study is aimed to find out the prevalence of dental caries based on gender, age, Black’s classification and its distribution on different teeth. Methods: This research is a descriptive research, conducted by collecting the data from patients’ medical records from Bagian Gigi dan Mulut in RSHS, Bandung and then analyzed the collected data. Results: The result of this study shows that Class I caries is the most common type of carious lesion (37.1%) and the mandibular molars are the most common teeth affected by caries (32.4%). Female is more prone to caries than males (60.5%) and the early adulthoods have the highest rate of caries occurrence (46.1%). Conclusion: It can be concluded that Class I caries is the most common type of carious lesion based on G. V. Black’s classification. Besides that, female is found to be more prone to caries than male and the early adulthoods had the highest rate of caries occurrence.